Impact of contact overlap on transconductance and noise in organic electrochemical transistors. (1st November 2019) - Polyravas, Anastasios G; Curto, Vincenzo F; Schaefer, Nathan; Calia, Andrea Bonaccini; Guimera-Brunet, Anton; Garrido, Jose A; Malliaras, George G
Abstract: Organic electrochemical transistors (OECTs) from poly(3, 4-ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) are used as amplifying transducers for bioelectronics. Although the impact on performance of device geometry parameters such as channel area and thickness has been widely explored, the overlap between the semiconductor film and the source and drain contacts has not been considered. Here we vary this overlap and explore its impact on transconductance and noise. We show that increasing contact overlap does not alter the magnitude of the steady-state transconductance but it does decreases the cut-off frequency. Noise was found to be independent of contact overlap and to vary according to the charge noise model. The results show that high-quality contacts can be established in PEDOT:PSS OECTs with minimal overlap.